THE ROLE OF COLLAGEN TRIPLE HELIX REPEAT-CONTAINING 1 PROTEIN (CTHRC1) IN RHEUMATOID ARTHRITIS - Myngbay, Askhat; Manarbek, Limara; Ludbrook, Steve; Kunz, Jeannette (International Journal of Molecular Sciences, 2021)
Rheumatoid arthritis (RA) is a chronic autoimmune disease causing inflammation of joints, cartilage destruction and bone erosion. Biomarkers and new drug targets are actively sought and progressed to improve available options for patient treatment. The Collagen Triple Helix Repeat Containing 1 protein (CTHRC1) may have an important role as a biomarker for rheumatoid arthritis, as CTHRC1 protein concentration is significantly elevated in the peripheral blood of rheumatoid arthritis patients compared to osteoarthritis (OA) patients and healthy individuals. CTHRC1 is a secreted glycoprotein that promotes cell migration and has been implicated in arterial tissue-repair processes. Furthermore, high CTHRC1 expression is observed in many types of cancer and is associated with cancer metastasis to the bone and poor patient prognosis. However, the function of CTHRC1 in RA is still largely undefined. The aim of this review is to summarize recent findings on the role of CTHRC1 as a potential biomarker and pathogenic driver of RA progression. We will discuss emerging evidence linking CTHRC1 to the pathogenic behavior of fibroblast-like synoviocytes and to cartilage and bone erosion through modulation of the balance between bone resorption and repair.
Keywords: Type of access: Open Access; collagen triple helix repeat containing 1; CTHRC1; rheumatoid arthritis; biomarker; bone erosion; cartilage destruction; fibroblast-like synoviocytes; Wnt signaling